PERSPECTIVES AND PRACTICES OF THE ENGLISH TEACHER ON ENGLISH LITERACY MATERIALS AND TEACHING AT ISLAMIC SECONDARY SCHOOL - Risma Anggraini; Sukri Adani (Nusantara Hasana Journal, 2024)
This research aims to discover teachers' perspectives about the meaning and application of teachers towards English literacy at Islamic Secondary Schools. This research is a descriptive study with a qualitative design. This study is aimed at exploring teachers' perspectives and their origins as determined by their positions and responsibilities within the MTsN 2 Southwest Aceh Regency, MTsN 3 Southwest Aceh Regency, and MTsN 4 Southwest Aceh Regency. The study will contribute to developing the teacher's perspective of English literacy and practices of teaching English literacy material. The study used the interview method to collect data from 6 English teachers from these 3 schools. The results show that there are similarities and differences in English literacy materials for grades 7,8, 9, and similarities between SMP and English literacy. There are differences in the language used in the two types of literacy. The conclusions of this study can be concluded that the teachers have a common understanding regarding how to teach English literacy in schools.